2015
DOI: 10.1021/acs.joc.5b01298
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactivity of Indolylmethylium Ions: Scope and Limitations in Synthetic Applications

Abstract: Eight substituted aryl(indol-3-yl)methylium tetrafluoroborates 3(a-h)-BF4 and three bis(indol-3-yl)methylium tetrafluoroborates 3(i-k)-BF4 have been synthesized and characterized by NMR spectroscopy and X-ray crystallography. Their reactions with π-nucleophiles 8(a-j) (silylated enol ethers and ketene acetals) were studied kinetically using photometric monitoring at 20 °C. The resulting second-order rate constants were found to follow the correlation log k(20 °C) = sN(N + E), in which nucleophiles are characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 72 publications
2
43
0
Order By: Relevance
“…[77] Recently we were also exploring, in collaboration with Dr. Barbero in Turin, other stabilized carbenium ions, [78] which were also studied by Mayr. [79] Again the electrophilicity was perfectly suitable for reactivity and for allowing the isolation of these stable carbenium ions.…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic S mentioning
confidence: 99%
“…[77] Recently we were also exploring, in collaboration with Dr. Barbero in Turin, other stabilized carbenium ions, [78] which were also studied by Mayr. [79] Again the electrophilicity was perfectly suitable for reactivity and for allowing the isolation of these stable carbenium ions.…”
Section: An Unexpected Journey: Carbenium Ions For Organocatalytic S mentioning
confidence: 99%
“…Recently, highly stabilized indoleninium ions 6 have been prepared, isolated, and characterized by direct condensation of arylaldehydes and indoles in the presence of non‐nucleophilic counteranions 9. Structural investigations and related kinetic studies of these ions in reactions with nucleophiles have also been reported 10. Apart from the aforementioned exceptions, intermediates 4 and 6 are generally too unstable to be isolated and therefore the elimination–addition process is generally carried out in a single synthetic operation.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Structural investigations and related kinetic studies of these ions in reactions with nucleophiles have also been reported. [10] Apart from the aforementioned exceptions, intermediates 4 and 6 are generally too unstable to be isolated and therefore the elimination-addition process is generally carried out in a single synthetic operation. The viability of this strategy depends on several factors, including the reactivity of electrophile 2 in the former F-C reaction and the aptitude of ZH to act as a good leaving group under different reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2 In this context, indolylmethanols have been recognized as a class of privileged building blocks for the synthesis of indole derivatives because this type of reactants can transform into highly reactive intermediates with resonance structures of carbocation, vinyliminium and delocalized cation in the presence of an acid, which have a tendency to be attacked by nucleophiles (Nu) and thus perform substitutions or cyclizations (Scheme 1). [3][4][5][6][7][8][9][10] However, most of the transformations employed 3-indolylmethanols as reactants since they can easily convert into vinyliminium intermediates, [3][4][5][6][7] which could even be isolated under some reaction conditions. 3,8 Thus, numerous 3-indolylmethanol-invovled transformations such as substitutions, 4 [3+2], 5 [3+3] 6 and [4+3] 7 cyclizations have been developed rapidly and well-established (eq.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] However, most of the transformations employed 3-indolylmethanols as reactants since they can easily convert into vinyliminium intermediates, [3][4][5][6][7] which could even be isolated under some reaction conditions. 3,8 Thus, numerous 3-indolylmethanol-invovled transformations such as substitutions, 4 [3+2], 5 [3+3] 6 and [4+3] 7 cyclizations have been developed rapidly and well-established (eq. 1).…”
mentioning
confidence: 99%